The association between health conditions and cannabis use in patients with opioid use disorder receiving methadone maintenance treatment. Issue 6 (November 2019) - Shams, Ieta; Sanger, Nitika; Bhatt, Meha; Rosic, Tea; Luo, Candice; Shahid, Hamnah; Mouravska, Natalia; Tam, Sabrina Lue; Hillmer, Alannah; Chawar, Caroul; D'Elia, Alessia; Hudson, Jacqueline; et al.
Abstract : Background: Cannabis is the most commonly used substance among patients in methadone maintenance treatment (MMT) for opioid use disorder. Current treatment programmes neither screen nor manage cannabis use. The recent legalisation of cannabis in Canada incites consideration into how this may affect the current opioid crisis. Aims: Investigate the health status of cannabis users in MMT. Method: Patients were recruited from addiction clinics in Ontario, Canada. Regression analyses were used to assess the association between adverse health conditions and cannabis use. Further analyses were used to assess sex differences and heaviness of cannabis use. Results: We included 672 patients (49.9% cannabis users). Cannabis users were more likely to consume alcohol (odds ratio 1.46, 95% CI 1.04–2.06, P = 0.029) and have anxiety disorders (odds ratio 1.75, 95% CI 1.02–3.02, P = 0.043), but were less likely to use heroin (odds ratio 0.45, 95% CI 0.24–0.86, P = 0.016). There was no association between cannabis use and pain (odds ratio 0.98, 95% CI 0.94–1.03, P = 0.463). A significant association was seen between alcohol and cannabis use in women (odds ratio 1.79, 95% CI 1.06–3.02, P = 0.028), and anxiety disorders and cannabis use in men (odds ratio 2.59, 95% CI 1.21–5.53, P = 0.014). Heaviness of cannabis use was not associated with health outcomes. Conclusions: Our results suggest that cannabis use is common and associated with psychiatric comorbidities and substance use among patients in MMT, advocating for screening of cannabis use in this population. Declaration of interest: None.